Character Education to Boost Quality of Students’ Soft Skill in English Class in Indonesia - Sari, Eka Dyah Puspita; Puspitasari, Indah; Purwandari, Gigih Ariastuti; Sari, Rosdiana Puspita (Soegijapranata Catholic University, 2023)
English language teaching (ELT) serves as a tool to teach students how to communicate in workplace. Character education taught in ELT can influence some of the ways students live in society, in terms of ethics, philosophy and principles. Moral education, as a part of character education, can be included in language learning and in character development in three important ways: integrated into school practice with an emphasis on literacy, socialized by moral content, and applied to course materials. This research provides description on developing human resources quality through character education. There are 38 respondents in this research, 36 students and 2 lecturers. They are chosen to obtain more objective data. The implementation of character education in teaching process happens from the planning to evaluating process. In planning, it shows that most students already know character education and its importance in higher education. In enacting process, most students implement moral values in their daily life. It makes their soft skill quality increase, both in personal and professional qualities. Last process is evaluating. In this process, some students think that the lecturers always help them internalize character education by implicitly including it in the problem sheet and the scoring rubrics.